2012
DOI: 10.1186/1752-0509-6-136
|View full text |Cite
|
Sign up to set email alerts
|

Robust synchronization control scheme of a population of nonlinear stochastic synthetic genetic oscillators under intrinsic and extrinsic molecular noise via quorum sensing

Abstract: BackgroundCollective rhythms of gene regulatory networks have been a subject of considerable interest for biologists and theoreticians, in particular the synchronization of dynamic cells mediated by intercellular communication. Synchronization of a population of synthetic genetic oscillators is an important design in practical applications, because such a population distributed over different host cells needs to exploit molecular phenomena simultaneously in order to emerge a biological phenomenon. However, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Remark 3.1 As far as we know, all the existing stochastic models concerning GONs [7,13,16,41] have considered the situation of Brownian motion. In this paper, the model discussed is universal, which replaces pure-diffusion Brownian motion with jump-diffusion Lévy process.…”
Section: T E K (T) (34)mentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 3.1 As far as we know, all the existing stochastic models concerning GONs [7,13,16,41] have considered the situation of Brownian motion. In this paper, the model discussed is universal, which replaces pure-diffusion Brownian motion with jump-diffusion Lévy process.…”
Section: T E K (T) (34)mentioning
confidence: 99%
“…[9] it is showed that synchronization can enhance the anticancer activity of 2-deoxyglucose in breast cancer cells due to an increase in cellular glucose metabolism. Therefore, it is not surprising that many theoretical analyses on synchronization with or without control have been established for GONs in these years [6,7,[10][11][12][13][14][15][16]. As we know, in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been clearly demonstrated that the generation of circa-dian rhythms at the suprachiasmatic nucleus is the result of the coupling of oscillators across the cellular and multicellular levels, 42 and a general framework for the emergence of synchronization in circadian cooperative systems employs non-linear coupled oscillators, resulting in phase-synchrony across large numbers of cells, 43 In neuronal networks, large scale simulations typically employ electrically phase-coupled systems that give rise to cooperative behaviors across large numbers of neurons 44 . Systems of genetic oscillators governing the synchronization of cells mediated by intercellular communication exhibit synchronous behaviors in spite of intrinsic parameter fluctuations and the presence of extrinsic noise 45 . Several novel behaviors have been noted, including phase synchronization within a system of weakly coupled self-sustained chaotic oscillators, suggesting that even under chaotic conditions, phases between individual oscillators can tend toward synchrony, 45 and there has recently been interest in the existence of “chimera states” in networks of coupled oscillators wherein a wide spectrum of complex states emerge from the underlying dynamics of a system of weakly coupled oscillators containing both synchronous and asynchronous elements 46 .…”
Section: Biological Clocks: Setting Life's Rhythmsmentioning
confidence: 99%
“…Hence, extrinsic noises resulting from environmental perturbations are unavoidable in modeling genetic oscillator networks (GONs). Based on linear matrix inequality (LMI) approach, the robust synchronization design problem for stochastic genetic oscillators has been discussed in Chen and Hsu (2012) to approximate the nonlinear coupled system. To exhibit more realistic characteristics of GONs, the stochastic synchronous criteria for Markovian jumping GONs with time delays have been derived in Wang et al (2010).…”
Section: Introductionmentioning
confidence: 99%